Adaptive fuzzy sliding mode controller for autonomous uderwater vehicles - Ge, Haoran. (2008)
This thesis presents an adaptive fuzzy sliding mode controller (AFSMC) for autonomous underwater vehicles (AUVs). Control of an AUV is a challenging problem due to the highly non-linear dynamics uncertain parameters and unpredictable external disturbances. Therefore, conventional control methods have not been very successful. The proposed adaptive fuzzy controller can approximate the unknown system dynamics and is robust against the model uncertainties and external disturbances. The adaptive hzzy sliding mode controller can be free from the system model and can achieve simple and fast control for complex nonlinear systems.